2019
DOI: 10.32890/jis.15.2019.8025
|View full text |Cite
|
Sign up to set email alerts
|

Malaysia-Indonesia Cross-Border Governance: Is There a Trade-off between Security and Economic Development?

Abstract: The National Security Council of Malaysia has declared the east coast of Sabah as the Eastern Sabah Security Zone (ESSZONE) to inhibit security threats and enhance security in the east coast of Sabah. This study employed an in-depth interview with the stakeholders involved in security governance and development in the study area. The selection of stakeholders was based on expert sampling. Secondary data relating to maritime economic activities were also used to reinforce the findings of the in-depth interview.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Another external threat facing the country is cross-border smuggling of goods and people. Anuar and Harun (2019) found that the country sees issues such as smuggling and cross-border drug trade that have been considered by Malaysia as one of the important security issues. But according to him, the country's commitment to deal with illegal drug smuggling activities at the Malaysia-Indonesia border has had a negative impact on the country's economy.…”
Section: Internal and External Threats At The Malaysianmentioning
confidence: 99%
See 1 more Smart Citation
“…Another external threat facing the country is cross-border smuggling of goods and people. Anuar and Harun (2019) found that the country sees issues such as smuggling and cross-border drug trade that have been considered by Malaysia as one of the important security issues. But according to him, the country's commitment to deal with illegal drug smuggling activities at the Malaysia-Indonesia border has had a negative impact on the country's economy.…”
Section: Internal and External Threats At The Malaysianmentioning
confidence: 99%
“…18 issued by Malaysia NSC detailing the specific roles and responsibilities of various agencies in managing terrorism. Anuar and Harun (2019) stated that NSC Malaysia has established NSC Directive No. 4 as one of the border management mechanisms that is not only for the purpose of dealing with the issue of smuggling and illegal trade of goods such as drugs but also other issues such as smuggling and human trafficking where through Ops Benteng, the Malaysian government has succeeded in cracking down on illegal immigrants and related illegals consistently.…”
Section: Security Management Structure At the Malaysianmentioning
confidence: 99%
“…Studies on formal and informal cross-border activities between Sebatik Malaysia-Indonesia for economic and social purposes have been examined by Anuar (2015), Sarma et al (2017), , , Harun (2019), andWan Shawaluddin et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Anuar and Harun (2019), the existence of cross-border activities in Sebatik Island and Sabah-KALTARA is further strengthened by the barter trade system under the Malaysia-Indonesia Border Trade Agreement 1970 andthe Border Cross Agreement (2006). In 2016, the Sabah state government suspended the barter trade system due to the increased frequency of kidnapping incidents in Sabah's eastern waters.…”
Section: Literature Reviewmentioning
confidence: 99%